The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12872-020-01748-y
|View full text |Cite
|
Sign up to set email alerts
|

Poor cardiovascular health status among Chinese women

Abstract: Background Systematic investigation and analysis of cardiovascular health status (CVHS) of Chinese women is rare. This study aimed to assess CVHS and atherosclerotic cardiovascular disease (ASCVD) burden in the Chinese women physicians (CWP) and community-based non-physician cohort (NPC). Methods In this prospective, multicenter, observational study, CVHS using the American Heart Association (AHA) defined 7 metrics (such as smoking and fasting glucose) and ASCVD risk factors including hypertension, hyperlipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…(6,8,12) A recent Chinese study showed compromised cardiovascular health in women after increased clustering of two or more risk factors during the climacteric period. (23) Among the seven risk factors considered, physical inactivity was the most prevalent. Similar results were observed in studies with a prevalence of 73.0% (11) and 84.0%, (22) identified among women who did not meet the target of at least 30 minutes of physical activity five times a week.…”
Section: ❚ Discussionmentioning
confidence: 99%
“…(6,8,12) A recent Chinese study showed compromised cardiovascular health in women after increased clustering of two or more risk factors during the climacteric period. (23) Among the seven risk factors considered, physical inactivity was the most prevalent. Similar results were observed in studies with a prevalence of 73.0% (11) and 84.0%, (22) identified among women who did not meet the target of at least 30 minutes of physical activity five times a week.…”
Section: ❚ Discussionmentioning
confidence: 99%